2006
DOI: 10.1167/iovs.05-0838
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Changes after Photodynamic Therapy

Abstract: In a primate model, under standard clinical parameters, a single PDT treatment resulted in various dynamic morphologic and functional retinal changes detectable for up to 9 months after treatment. The significance of the observed changes and possible ways of pharmacologic interference with PDT adverse effects are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 60 publications
1
38
0
3
Order By: Relevance
“…It has been shown that shortly after its application, PDT results in the breakdown of vascular barriers caused by damage to the vascular endothelial cells and pericytes; this occurs first in the CNV and subsequently in the surrounding normal choriocapillary network. Functional damage to the retinal pigment epithelium (RPE) also occurs [10][11][12]. All of these changes can lead to an increase of subretinal fluid accumulation that appears as an intensive indocyanine green hyperfluorescence during indocyanine green angiography (ICGA), which is obtained shortly after PDT [5].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that shortly after its application, PDT results in the breakdown of vascular barriers caused by damage to the vascular endothelial cells and pericytes; this occurs first in the CNV and subsequently in the surrounding normal choriocapillary network. Functional damage to the retinal pigment epithelium (RPE) also occurs [10][11][12]. All of these changes can lead to an increase of subretinal fluid accumulation that appears as an intensive indocyanine green hyperfluorescence during indocyanine green angiography (ICGA), which is obtained shortly after PDT [5].…”
Section: Discussionmentioning
confidence: 99%
“…RPE atrophy, juxtafoveal CNV, and transient reduction in macular function demonstrated by mERG led investigators to reconsider PDT parameters for the treatment of CSC. 51,53,138,139 Lai et al 140 reduced the dosage of verteporfin and shortened the interval between infusion and laser application to induce choroidal vascular remodelling and minimise any collateral damage to adjacent retinal structures. The safe and beneficial effect of 'safety enhanced' (half-dose verteporfin)-PDT was demonstrated in both acute and chronic CSC by the same investigators.…”
Section: Photodynamic Treatment With Verteporfinmentioning
confidence: 99%
“…Indeed, adverse effects by verteporfin PDT have been reported (Tzekov et al, 2006, Ozdemir et al, 2006, Oner et al, 2005a, 2005b in clinical situation. To enhance PDT effects and minimize damage of normal tissues, highly selective targeting might be necessary.…”
Section: Visudyne ®mentioning
confidence: 99%